P-152 The first morphokinetic map of human abnormal fertilisation. (30th June 2022) - Takahashi, T; Shimazaki, K; Tanimura, Y; Amagai, A; Sawado, A; Akaike, H; Mogi, M; Kaneko, S; Kato, M; Okimura, T; Miki, T; Ezoe, K; et al.
Abstract: Study question: What are the similarities and differences between the morphokinetics of abnormal, one- (1PN) and three-pronuclear (3PN) and normal bi-pronuclear (2PN) fertilisation? Summary answer: The morphokinetic analysis of 1PN/3PN fertilisation reveals novel aspects of abnormal early development. What is known already: Assisted reproduction technology has allowed the observation of early human development. Initially assessed statically at a single time point, fertilization has revealed its complexity once observed by Time-Lapse Microscopy (TLM). Detailed morphokinetic analysis of fertilisation has been reported in the last few years, unveiling previously unknown cytoplasmic phenomena (e.g. the cytoplasmic wave and halo) and the importance of cell symmetry for embryo development. At present, abnormal fertilization remains neglected, despite potential for understanding the physiology and pathology of early human development. Study design, size, duration: This retrospective study involved TLM observation of normally (2PN, n = 2, 685) and abnormally (1PN, n = 41; 3PN, n = 127) fertilised oocytes generated in ICSI cycles. Oocyte retrievals were carried out after the clomiphene citrate-based minimal ovarian stimulation, between October 2019 and December 2020. Oocytes of patients with different diagnoses of infertility were included in the analysis, while cases involving cryopreserved gametes or surgically retrieved sperm were excluded. Participants/materials, setting, methods: Microinjected oocytes were assessed by a combined TLM-culture system (Embryoscope). Oocytes not suitable for TLM assessment, due to excess of residual corona cells or inadequate orientation for correct observation, were not analysed. Phenomena, relevant to meiotic resumption, pronuclear dynamics, cytoplasmic/cortical modifications, cleavage pattern, and embryo quality, were annotated and compared between groups. Main results and the role of chance: Second polar body (PBII) extrusion was observed in all 1PN- and in a majority of 3PN-zygotes (92.1%). A 0.3-hour delay in PBII extrusion was confirmed in 3PN-zygotes (P = 0.0439). In a significant proportion of 3PN-zygotes, a third (female) PN formed from reabsorption of the PBII. The cytoplasmic wave was observed not only in 2PN- and 3PN-, but also in 1PN-zygotes. The presence and position of cytoplasmic halo were comparable among the three classes of zygotes. However, the duration of the cytoplasmic halo was prolonged in 1PN-zygotes (P < 0.0001). PN juxtaposition immediately before PN breakdown was less frequent in 3PN- compared with 2PN-zygotes (P = 0.0159). Furthermore, asynchronous PN breakdown was increased in 3PN- compared with 2PN-zygotes (P = 0.0026). The PN area of 1PN- was larger than that of 2PN-zygotes; however, the PN area of 3PN-zygotes was smaller than that of 2PN-zygotes. In 1PN-zygotes, a developmental delay was observed starting from the disappearance of the cytoplasmic halo, reaching 9 hours at the time of cleavage (P < 0.0001). A higher incidence of abnormal cleavage (P = 0.0019) and blastomere fragmentation (P < 0.0001) was observed in 1PN-zygotes. Cleavage progression was increasingly affected especially in 1PN-zygotes, resulting in blastocyst formation rates of 70.2%, 12.2% and 53.5% in 2PN-, 1PN- and 3PN-zygotes, respectively (P < 0.0001). Limitations, reasons for caution: The study data derive from treatments carried out in a single centre. The study findings therefore require independent verification from other research groups. Wider implications of the findings: These observations suggest that 1PN and 3PN fertilisation follow the general pattern of normal fertilization. Crucially, they also shed light on diverse and previously undescribed phenomena - e.g. reabsorption of the PBII in 3PN zygotes - underpinning the origins of abnormal fertilization and potentially clinically relevant. Trial registration number: not applicable